Свободные вращения абсолютно твердого цилиндра с учетом вязкого трения - Гладков, С. В.; Науменко, К. В. (НТУ "ХПИ", 2006)
Free rotations of rigid cylinder with viscous friction were considered in the article. It was given analytical solution for vector of right angular velocity and numerical solution for position vector using Runge-Kutta 4-5th order method in Maple. Analytical and numerical solutions were compared and it was shown high accuracy of numerical methodic, which was the result of using of rotation vector rather then rotation tensor or Euler's arcs
Keywords: коротковолокнистые композиционные материалы; сила трения; тензор поворота; угловая скорость